The Role of Change Management and HR Strategy in Enhancing Teacher Performance during Curriculum Reform - Juliastuti Juliastuti; Ai Rukmini; Prihantini Prihantini; Amalia Mustika; Juliastuti Juliastuti; Ai Rukmini; Prihantini Prihantini; Amalia Mustika (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study investigates how change management and strategic human resource (HR) practices interact to enhance teacher performance during the implementation of the Independent Curriculum in Indonesian public senior high schools. While prior research has examined curriculum reform and teacher performance separately, limited empirical attention has been given to the structural integration of organizational change processes and HR strategies within a unified analytical model. Addressing this gap, the study adopts a mixed methods approach using an explanatory sequential design. Quantitative data were collected from 250 teachers across public schools in the Greater Jakarta (Jabodetabek) area and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Qualitative data from semi-structured interviews were subsequently analyzed through thematic analysis to contextualize the statistical findings. The results reveal that Change Management significantly influences HR Strategy (β = 0.71, p < 0.001), and HR Strategy significantly affects Teacher Performance (β = 0.63, p < 0.001). The indirect effect indicates partial mediation, suggesting that HR practices serve as a key mechanism translating organizational readiness into improved instructional outcomes. The model explains 68% of the variance in Teacher Performance (R² = 0.68), indicating substantial explanatory power. Qualitative findings further highlight the critical role of leadership, digital capacity development, and institutional support in sustaining reform implementation. The study contributes theoretically by positioning change management as a structural antecedent and HR strategy as a mediating mechanism in educational reform. These findings offer a systemic framework for understanding curriculum transformation as an organizational capability-building process rather than solely a pedagogical adjustment.